Menggali Motivasi Serta Menghadapi Hambatan Dalam Pembelajaran Bahasa Arab Sebagai Bahasa Kedua - Fitriyah, Afiyatul; Taufik (Universitas KH. Mukhtar Syafaat, 2024)
This study aims to identify strategies to increase student motivation in learning Arabic as a second language, as well as how to overcome obstacles that may arise during the learning process. The research method used is literature analysis which includes reading and analyzing relevant information in order to gain knowledge about the research topic. This study found that student motivation is influenced by several factors such as student attitude, clear learning goals, learning quality, and external support. One strategy to improve students' motivation is to use interactive learning methods, project-based learning, and educational technology. In addition, improving Arabic learning also includes consistent utilization of guidance, increased access to information, and utilization of technology. As a result, this study provides important information about the factors that influence student motivation and effective strategies to overcome the challenges of learning Arabic as a second language, with the aim of improving student learning outcomes and making a positive contribution to the development of Arabic language education.